Mass transfer and dispersion around an active cylinder in cross flow and buried in a packed bed - J. M. P. Q. Delgado (2006)
The present work describes the mass transfer process between a moving fluid and a slightly soluble cylinder, with the axis perpendicular to flow direction, buried in a packed bed of small inert particles, with uniform voidage. Fluid flow in the packed bed around the cylinder was assumed to follow Darcys law and, at each point, dispersion of solute was assumed to be determined by radial and axial dispersion coefficients, in the cross-stream and streamwise directions, respectively. Numerical solutions of the differential equation describing solute mass conservation were undertaken to obtain the concentration field near the soluble surface and the mass transfer flux was integrated to give the Sherwood number as a function of the relevant parameters. Mathematical expressions are proposed that describes accurately the dependence found numerically between the value of the Sherwood number and the values of Peclet number, Schmidt number and the ratio between the diameter of cylinder and the diameter of inerts.